Investigating the individual interests of undergraduate students in STEM disciplines - Ammar, Mohammad; Siby, Nitha; Khalili, Sara; Al-Thani, Alshayma N.; Sellami, Abdellatif; Touati, Farid; Bhadra, Jolly; Al-Thani, Noora J.; Ahmad, Zubair (Frontiers in Education, 2024)
Despite massive investments in the education sector to empower youth in Qatar, a vital concern remains to retain students in science, technology, engineering, and mathematics (STEM) disciplines at the undergraduate level. Even though the country is committed to fostering a knowledge-based society, the low interest of undergraduates in STEM disciplines remains a vital challenge. To investigate this, the current study uses a survey methodology to investigate the perspectives of 172 undergraduate students to understand quantitatively the factors that influence their individual interests in STEM disciplines. Non-parametric significance tests and binary logistic regressions were employed to quantitatively measure the direct factors and predictors that affect students’ individual interests. Findings indicated that aspects like students’ reason/motivation to join STEM, their interaction with faculty, the habit of skipping classes, the difficulty faced in the curriculum, and their parents’ highest educational qualification have an association with individual interests. Also, it was found that demographics such as age group, ethnicity, undergraduate discipline, undergraduate year, parent’s employment status, and mother’s highest educational qualification do not contribute to significant differences in students’ individual interests. These conclusions provide important implications for educationists and policymakers to devise constructive reforms to enhance undergraduate students’ individual interests, thereby improving their persistence in STEM.